Variation in appropriate diabetes care and treatment targets in urban and rural areas in England: an observational study of the 'rule of halves'. Issue 2 (16th February 2022) - Mason, Thomas; Whittaker, William; Dumville, Jo C; Bower, Peter
Abstract : Objectives: To estimate the 'rule of halves' for diabetes care for urban and rural areas in England using several data sources covering the period 2015–2017; and to examine the extent to which any differences in urban and rural settings are explained by population characteristics and the workforce supply of primary care providers (general practices). Design: A retrospective observational study. Setting: Populations resident in predominantly urban and rural areas in England (2015–2017). Participants: N=33 336 respondents to the UK Household Longitudinal Survey in urban and rural settings in England; N=4913 general practices in England reporting to the National Diabetes Audit and providing workforce data to NHS Digital. Outcomes: Diabetes prevalence; administrative records of diagnoses of diabetes; provision of (all eight) recommended diabetes care processes; diabetes treatment targets. Results: Diabetes prevalence was higher in urban areas in England (7.80% (95% CI 7.30% to 8.31%)) relative to rural areas (7.24% (95% CI 6.32% to 8.16%)). For practices in urban areas, relatively fewer cases of diabetes were recorded in administrative medical records (69.55% vs 71.86%), and a smaller percentage of those registered received the appropriate care (45.85% vs 49.32%). Among estimated prevalent cases of diabetes, urban areas have a 24.84% achieving these targets compared with 25.16% in rural areas. However, adjusted analyses showed that the performance of practices in urban areas in providing appropriate care quality was not significantly different from practices in rural areas. Conclusions: The 'rule of halves' is not an accurate description of the actual pattern across the diabetes care pathway in England. More than half of the estimated urban and rural diabetes population are registered with clinical practices and have access to treatment. However, less than half of those registered for treatment have achieved treatment targets. Appropriate care quality was associated with a greater proportion of patients with diabetes achieving treatment targets.